Coffee consumption and lifestyle factors associated with hypertension risk in working-age residents of Tanjung Gusta, Medan - Ulan Azmi; Eva Ellya Sibagariang; Hartono Hartono (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Hypertension is a non-communicable disease with increasing prevalence, including among productive age adults. Coffee consumption habits and unhealthy lifestyles are suspected to increase the risk of hypertension. This study aimed to determine the relationship between coffee consumption and lifestyle with the incidence of hypertension among productive age adults in Tanjung Gusta Village, Medan City.  Method: This quantitative study used a cross-sectional design. The sample comprised 98 respondents selected using accidental sampling. Data were collected through structured questionnaires and blood pressure measurement using a sphygmomanometer. Data were analyzed using the chi-square test with a significance level of 0.05. Results: Among 98 respondents, 18 (18.4%) had hypertension. Coffee consumption was significantly associated with hypertension (p=0.033), and lifestyle was also significantly associated with hypertension (p=0.041). Respondents who frequently consumed coffee and had unhealthy lifestyles showed higher proportions of elevated blood pressure. Conclusion: There are significant relationships between coffee consumption and lifestyle with the incidence of hypertension among productive age adults in Tanjung Gusta Village, Medan City. Limiting coffee intake and adopting a healthy lifestyle are recommended for hypertension prevention.